Food Retailers as Key Actors - Oosterveer, Peter (Ökologisches Wirtschaften - Fachzeitschrift, 2008)
All kinds of food products are easily accessible throughout the year in the outlets of global retailing firms. Nowadays, as most people shop for food in supermarkets, the retail sector is also assuming a dominant role in sustainable food consumption. Can they fulfill this role and how can they realize it?
Keywords: Transition; Sustainable Food; Consumption; Food Retailers